Blue box. Volume 1 - Miura, Kōji, 1995- (Shonen Jump graphic novel., 2022)
A badminton guy falls for a basketball girl. Do these sports-crossed lovers have a chance? Taiki Inomata loves badminton, but he has a long way to go before he can reach nationals. When Taiki sees upperclassman Chinatsu Kano practicing her heart out on the girls' basketball team, he falls for her hard. After an unexpected turn of events brings the two closer together, sports might not be the first thing on their minds anymore! Taiki admires Chinatsu from afar, but he doubts that she sees him in the same way. Yet somehow, he musters up the courage to tell her to never give up on her dreams! After such a bold declaration, will Taiki's fleeting high school romance finally begin?